Integrasi Logika Matematika dan Nilai-Nilai Keislaman dalam Pengembangan Media Pembelajaran Berbasis Android - Fahruh Juhaevah (Jurnal Dimensi Pendidikan dan Pembelajaran, 2021)
Students' efforts to produce instruction media should be supported by the quality of the resulting learning media and can integrate the concept of mathematical logic and the islamic values based on the objectives of the instruction media course. The purpose of this research is to accommodate students to produce quality and integrative instruction media against the concepts of mathematical logic and the islamic values. The research method used is plomp development model. The results showed that the resulting learning media meets the criteria of quality media based on 1) validity covering aspects of content, language, and media, 2) practicality covering aspects of ease of use, attractiveness, and efficiency, 3) effectiveness based on improved student test results. In addition, developed instruction media has met integration indicators with integrative categories.